Abandono familiar y su repercusión en el estado emocional de un adulto de 70 años en la Parroquia San Carlos - Lema Chele, Lissete Solange (2023)
In the present case study, a theory is projected that helps to interpret depression in the elderly to understand and distinguish it, the aspects of the family in which the elderly develop and their correlation with their emotional aspect are also formulated. Themes are displayed that show emotional imbalances in the elderly with different authors from previous projects, elementally when family abandonment is exhibited in them, in terms of how this problem has consequences and, in turn, the link that exists with depression. The subsequent behavior of abandonment and depression of the elderly is taken into account, concluding that it is verified that depression is related to the abandonment of the elderly. Subsequently, an intervention plan is taught whose objective is to avoid the increase in depression caused by family abandonment, in the same way it seeks to provide the elderly with tools and ways to confront aspects of family abandonment and its correlation with depression. The therapeutic plan proposed for this case study is Cognitive Behavioral Therapy, through which it is possible to obtain improvement in their mental state, with notable changes in their behavior, reaching the goal proposed at the beginning of the intervention.